(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Education is basic necessityfor survival just as food, clothing and shelter, education is equally essentialwith other necessities mainly for self-sustenance, dignity and growth. Theframer of the Constitution realized the importance of education and has imposeda duty on the state under Article 45 of Directive Principle of State Policy toprovide fee and Compulsory education to all children until they complete theage of 14 years within 10 years from the commencement of the Constitution. Inthe context of child right movement, there had been continuous advocacydemanding the education should be made a fundamental right. Even activists ofthe child labour movement joined this campaign. Such advocacy and campaigningled to the Unni Krishnan Judgment. In an unprecedented manner, the SupremeCourt establishes new Human Right Jurisprudence. Article 45 which was anEconomic Social and Political Cultural right under DPSP was read with Article21, a Civil and Political, Fundamental Right, thus making education anenforceable Fundamental Right.